2011
DOI: 10.1029/2010gl045736
|View full text |Cite
|
Sign up to set email alerts
|

“Shamal” swells in the Arabian Sea and their influence along the west coast of India

Abstract: Wave data collected off Ratnagiri, Goa and Dwarka along the west coast of India during winter season (NE monsoon and early pre‐monsoon) present distinct wave characteristics with periodicity ranging between 2 and 5 days associated with shamal events. The notable wave characteristics during these events are: an increase in wave height, decrease in swell period and a common propagation direction (northwest) for wind sea and swell. IFREMER/CERSAT blended winds clearly show the presence of strong northwesterly win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
41
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 97 publications
(47 citation statements)
references
References 13 publications
6
41
0
Order By: Relevance
“…Kurian and Baba (1987) showed the importance of shelf slope in controlling spatial contrasts in bottom frictional attenuation and consequently the coastal energy regime. Wave heights along the WCI are generally low during NE and pre-monsoon seasons, and higher during SW monsoon (Aboobacker et al, 2011;Vethamony et al, 2009;Kumar and Kumar, 2008). Waves along the WCI are generally multi-peaked (Kumar et al, 2003), which is due to co-existence of swell and wind sea (Vethamony et al, 2009).…”
Section: S S S S S S S S S Smentioning
confidence: 99%
See 1 more Smart Citation
“…Kurian and Baba (1987) showed the importance of shelf slope in controlling spatial contrasts in bottom frictional attenuation and consequently the coastal energy regime. Wave heights along the WCI are generally low during NE and pre-monsoon seasons, and higher during SW monsoon (Aboobacker et al, 2011;Vethamony et al, 2009;Kumar and Kumar, 2008). Waves along the WCI are generally multi-peaked (Kumar et al, 2003), which is due to co-existence of swell and wind sea (Vethamony et al, 2009).…”
Section: S S S S S S S S S Smentioning
confidence: 99%
“…Waves along the west coast of India (WCI) are dominated by swells during southwest (SW) and northeast (NE) monsoon seasons and by wind seas during pre-monsoon season (Vethamony et al, 2011;Kumar et al, 2000;Rao and Baba, 1996). Kurian and Baba (1987) showed the importance of shelf slope in controlling spatial contrasts in bottom frictional attenuation and consequently the coastal energy regime.…”
Section: S S S S S S S S S Smentioning
confidence: 99%
“…The waves along the west coast of the Indian subcontinent primarily depend on the wind conditions prevailing over the three different seasons: southwest (SW) monsoon (June-September), northeast (NE) monsoon (OctoberJanuary) and pre-monsoon (February-May). The general wave conditions in the Arabian Sea during the pre-monsoon period also depend on the swells coming from the far northwest (NW) Arabian Sea because of the northwesterly blowing Shamal winds (Aboobacker et al 2011). According to Aboobacker et al (2011), NW waves are observed along the west coast of India with mean periods ranging between 6 and 8 seconds.…”
Section: Introductionmentioning
confidence: 99%
“…The general wave conditions in the Arabian Sea during the pre-monsoon period also depend on the swells coming from the far northwest (NW) Arabian Sea because of the northwesterly blowing Shamal winds (Aboobacker et al 2011). According to Aboobacker et al (2011), NW waves are observed along the west coast of India with mean periods ranging between 6 and 8 seconds. These waves are due to the strong northwesterly winds blowing in the Arabian peninsula and the northwestern Arabian sea, and result in increase in wave height, decrease in swell period and common NW direction during the NE monsoon and early pre-monsoon season.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation